Frequency dispersion and temperature dependence of electrical behaviours in 0.4Bi(Ni1/2Zr1/2)O3–0.6PbTiO3. Issue 10 (July 2020) - Wei, Yongxing; Bai, Chenxing; Jin, Changqing; Zhu, Weitong; Hu, Lin; Nan, Ruihua; Dai, Zhonghua
Abstract: In this study, the temperature dependence of dielectric behaviours and the polarisation and electrostrain responses of 0.4Bi(Ni1/2 Zr1/2 )O3 –0.6PbTiO3 (0.4BNZ–0.6PT) were studied to better understand their electrical performance. A Rietveld refinement analysis of the XRD pattern, supported by bright-field TEM images, suggests the coexistence of tetragonal and pseudocubic phases. Above 398 K, the normalised piezoelectric coefficient ( d 33 ∗ ) increases due to heating, reaching 941 pm/V at 453 K. Most importantly, 0.4BNZ–0.6PT displays obvious frequency dispersion in the ferroelectric state. A low-temperature dielectric anomaly occurred at approximately 175 K that was related to the origin of the frequency dispersion. The planar electromechanical coupling constant ( k p ) also changed considerably after heating, increasing from 0.14 at 90 K to 0.43 at 300 K. This indicates an intrinsic relationship between the dielectric and piezoelectric behaviours. Our study demonstrates that there is a significant difference between typical ferroelectrics and the ferroelectric state of 0.4BNZ–0.6PT relaxor ferroelectrics.